Removal of Trihalomethanes from Aqueous Solution through Adsorption and Photodegradation - S.M. Yakout (Adsorption Science & Technology)
Trihalomethanes (THMs) are carcinogenic by-products of disinfection that are present in drinking water. In the present research, adsorption and photodegradation, either individually or in tandem, were employed for the removal of the principal THMs found in water supply systems. The effects of pH, contact time, adsorbents and adsorbate concentration on the adsorption system were investigated. The Langmuir and Freundlich adsorption isotherm models were used to analyze the resulting adsorption data. Photodegradation of THMs was carried out in the presence and absence of activated carbon. The integration of adsorption and photodegradation systems as a hybrid treatment process resulted in a synergetic enhancement of the THM removal efficiency. The kinetics of THM removal were found to follow the pseudo-second-order model rather than the Langmuir–Hinshelwood pseudo-first-order model.